Wheat Crop Response to Liming and N and P Fertilization of Acidic Soils in Tsegede Highlands of Tigray Region, Ethiopia - Hadera, Abreha Kidanemariam (Soil Acidity Characterization and Effects of Liming and Chemical Fertilization on Microbial Growth, Nutrient Uptake and Yield of Wheat (Triticum aestivum L.): The Case of Acidic Soils in Tsegede District, Northern Ethiopia, Edition 1, 2024)
The presence of highly weathered acidic soils in Ethiopia has been constraining wheat crop production. A study was conducted to evaluate wheat yield response to lime and N and P fertilizer applications and to determine the effects of residual lime on the grain yield of wheat and the chemical properties of acidic soils in the Tsegede highlands of northern Ethiopia. Three lime rates (without lime, half and full recommended lime) and four recommended N and P fertilizer levels (without N and P, 46 kg ha-1 N, 20 kg ha-1 P, and 46 kg ha-1 N + 20 kg ha-1 P) were evaluated in a randomized complete block design with three replicates. Results showed that wheat yield and yield components, N and P fertilizer uptake efficiency, and chemical properties of the acidic soils were significantly (P \(\le\) 0.05) affected by the main effects of fertilizer, lime, and residual lime. The highest biomass yield, grain yield, N and P uptake, agronomic efficiency and apparent recovery efficiency of N and P fertilizers were documented in the plots that received combined NP fertilizers + full recommended lime followed by NP fertilizers + half recommended lime and only P + full recommended lime while the lowest values were recorded in the control and in the plots that received only N fertilizer. Moreover, the plots with the residual lime of the full recommended rate applied in the preceding year and supplemented with NP fertilizers gave significantly (P \(\le\) 0.05) higher grain yield than the control by about 437%. When comparing the second cropping season to the previous one, the average wheat grain yield decreased by 34%. Similarly, soil OM and exchangeable acidity increased by 27% and 2.01 units, respectively, whereas soil pH, accessible P, exchangeable Ca, and Mg decreased by 0.15 units, 20%, 30%, and 28%. Therefore, it is proposed that applying lime and NP fertilizers together could result in the Tsegede highlands producing wheat crops in a sustainable manner. Hence, it is suggested that sustainable wheat crop production in the Tsegede highlands could be achieved by combined application of lime with NP fertilizers.